Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2207688
|View full text |Cite
|
Sign up to set email alerts
|

Tales from the front lines of a large-scale serious game project

Abstract: Serious games have received much positive attention; correspondingly, many researchers have taken up the challenge of establishing how to best design them. However, the current literature often focuses on best practice design strategies and frameworks. Fine-grained details, contextual descriptions, and organisational factors that are invaluable in helping us to learn from and reflect on project experiences are often overlooked. In this paper, we present five distinct and sometimes competing perspectives that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 28 publications
0
33
0
2
Order By: Relevance
“…The former line of research has resulted in several theories of human behavior (e.g. [1,31,33]), whereas the latter has resulted in several persuasive games that have shown to be effective tools for promoting health and wellbeing by effecting behavior change in a desired manner [17,24,25,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former line of research has resulted in several theories of human behavior (e.g. [1,31,33]), whereas the latter has resulted in several persuasive games that have shown to be effective tools for promoting health and wellbeing by effecting behavior change in a desired manner [17,24,25,29].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this growing interest in game-based interventions for behavior change, current persuasive games suffer two major limitations: first, although research has shown that interventions that are informed by theories and models tend to be more successful than those based on intuition [16], most persuasive games to date are not based on the theories of what motivates behavior change (e.g., [24,25]). This makes it difficult to evaluate what persuasive approaches worked and why they worked.…”
Section: Introductionmentioning
confidence: 99%
“…Village Voices is intended to teach children about conflict resolution management [17]. It is a multiplayer open world game that takes place in a virtual village, and emphasises friendship, reputation management, interdependence, and mastery of conflict resolution.…”
Section: Example: Village Voicesmentioning
confidence: 99%
“…Designing educational experiences is difficult because there are a number of different perspectives and concerns that need to be balanced [13,30]. Taking an educational design in one direction may cause some other aspect to swing out of balance.…”
Section: Introductionmentioning
confidence: 99%
“…Having a theoretical grounding while designing can provide a context for discussing design issues and how they might impact the numerous components of an educational game's design; however, a theoretical framework alone will not guarantee that a game achieves its ultimate goals. Throughout the design process, factors inherent in normal design iteration can impinge upon the design and cause conflicts between different components [13]. While having a design framework can inform what redesign options educational game designers might have for addressing a given design conflict, it may not easily inform them which option is most valuable to explore.…”
Section: Introductionmentioning
confidence: 99%